TI_GERICHTE 11.2020.52 vom 28. Februar 2022 , Riscatto o spostamento di una servitù di passo pedonale gravante il fondo serviente - TI Tribunale d'appello (2022)
Riscatto o spostamento di una servitù di passo pedonale gravante il fondo serviente